Emotion-focused ego-state coaching reduces communication apprehension: evidence from a randomized controlled study - Eilert, Dirk W.; Mensah, Philipp; Schmäh, Marco (Frontiers in Organizational Psychology, 2025)
BackgroundCommunication apprehension (CA) is a widespread phenomenon negatively affecting communicative skills, psychological well-being, and social connectedness. This randomized controlled study investigated whether online emotion-focused ego-state coaching, based on the emTrace framework, can sustainably reduce CA.MethodsA total of 260 German-speaking participants with elevated CA were randomly assigned to one of two ego-state coaching interventions: Core Transformation (CT) or Smart Part Lab (SPL). CA was assessed using the PRCA-24 and a bipolar scale of subjective feeling at pretest, posttest, and 2-week follow-up.ResultsBoth interventions significantly reduced CA [F(2, 258.3) = 242.14, p < 0.001; pre: M = 80.7; post: M = 63.4; follow-up: M = 62.3; η2p = 0.65), with 80% of initially high-CA participants reporting moderate or low CA at follow-up. CT induced stronger self-transcendent experiences than SPL; however, this did not translate into a stronger CA reduction, suggesting self-transcendence is not the primary mechanism of change.ConclusionA single 80-min online ego-state coaching session within the emTrace framework sustainably reduced trait-like CA. The findings highlight the potential of resource-oriented, emotion-focused coaching as a low-threshold intervention to foster communicative confidence and psychological resilience.